The Scientific Field During Argentina’s Latest Military Dictatorship (1976–1983): Contraction of Public Universities and Expansion of the National Council for Scientific and Technological Research (CONICET) - Bekerman, Fabiana Andrea (2013)
This study looks at some of the traits that characterized Argentina’s scientific and university policies under the military regime that spanned from 1976 through 1983. To this end, it delves into a rarely explored empirical observation: financial resource transfers from national universities to the National Scientific and Technological Research Council (CONICET, for its Spanish acronym) during that period. The intention is to show how, by reallocating funds geared to Science and Technology, CONICET was made to expand and decentralize to the detriment of universities. This was the primary tool used by the military regime to thwart higher education’s research development, bolstering research efforts at other realms. Thus, CONICET grew in budget, number of researchers, and staff size, creating new research institutes, while national universities struggled with reduced funding and were forced to shut down their institutes and programs. As a result, CONICET virtually concentrated all scientific research, foregoing the knowledge accumulated at universities, which drove a wedge between both institutions. This military approach to science and technology policy-making is discussed, bearing in mind the notion of dependence—both in terms of the state’s intervention in the inner workings of the scientific-university field as well as regarding the role played by international financial support in scientific research development.